Farmers' societies and agricultural development - Desai, R. G. 1951- (Allahabad, India : Chugh Publications, 1988)
Evaluation study on the performance of selected farmers' service societies in Bellary District, Karnataka.
Revision of the author's thesis (Ph. D.--Gulbarga University, Gulbarga, Karnataka, 1986)
Bibliography: p. 180-182.
Keywords: Farmers -- India -- Bellary (District) -- Societies, etc; Agriculture -- India -- Bellary (District) -- Societies, etc